(untitled) (Research, Society and Development, 2023)
The activities necessary for motor stimulation are developed at school through the execution of movements worked on in class in order to stimulate students in the development of motor skills. Thus, this research aims to analyze the level of motor development of students in the early years of elementary school using the TGMD-2 test as an instrument for assessing motor performance. The results obtained in this study demonstrate that large parts of the sample of evaluated students obtained an unsatisfactory level in fundamental motor skills, in which it can be observed that there is a large number of students who do not have adequate motor development for their age. These results are directly related to the current situation of children in Brazil regarding low motor competence.